Chondrocyte enlargement is a marker of osteoarthritis severity. Issue 8 (August 2019) - Gratal, P.; Mediero, A.; Sánchez-Pernaute, O.; Prieto-Potin, I.; Lamuedra, A.; Herrero-Beaumont, G.; Largo, R.
Summary: Objective: We aimed to assess whether an increase in chondrocyte size might be a feature of the articular cartilage (AC) hypertrophic-like phenotype both in experimental and in human osteoarthritis (OA). The anatomical location of these enlarged cells in the cartilage layers was also evaluated. Methods: Experimental OA was carried out in female rabbits alone or in combination with osteoporosis (OPOA). The rabbits were subjected to destabilization knee surgery to develop OA. Osteoporosis was induced with ovariectomy and methylprednisolone administration. Human OA samples obtained from knee replacement surgery were also studied. Cartilage lesions and chondrocyte size were assessed in AC sections. Immunostaining of type-X collagen and metalloproteinase-13 were used as markers of the AC hypertrophic transformation. Both the cell size and the gene expression of type-X collagen were further analyzed in primary murine chondrocyte cultures. Results: Compared to healthy AC, chondrocyte size was increased both in experimental and in human OA, in correlation with the severity of cartilage damage. No differences in chondrocyte size were found between deeper or more superficial regions of AC. In cell cultures, accretion of hypertrophic markers and cell enlargement were found to occur synchronized. Conclusions: We observed an enhancement in the mean size of chondrocytes at the OA cartilage, which showed correlation with cartilage damage, both in human and in experimental OA. The enlarged chondrocytes were homogeneously distributed throughout the AC. Our results suggest that chondrocyte size could be a reliable measure of disease progression, of potential use in the histopathological assessment of OA cartilage.